Spatialising the ecological impacts of alien species into risk mapsGitHub - Océane Boulesnane-Guengant; Mathieu Rouget; Antoine Becker-Scarpitta; Christophe Botella; Sabrina Kumschick (Global Ecology and Conservation)
Spatial assessments of the ecological impacts of alien species are needed to integrate impacts into biodiversity conservation policies and management strategies. We developed standardised approaches for aggregating impact scores at both species and site levels, synthesising the ecological impacts of alien species into risk maps. We applied these approaches to 33 Australian Acacia species introduced in South Africa. Creating risk maps involves four main steps: (1) perform impact assessment per species; (2) combine impact categories into one score per species; (3) gather species occurrence data into standardised grid cells; and (4) combine impact scores across species per grid cell into a risk map. We proposed six risk maps based on different assumptions of impact aggregation. All risk maps revealed important variation in environmental impacts of alien Acacia species across South Africa. The only exception was the precautionary risk map, which indicated that nearly all the areas occupied by Acacia had high risk, whereas the other risk maps identified between 5 % and 14 % with high risk. Risk maps provide additional information compared to maps of alien species richness and can help identifying areas where greater ecological impacts are likely. The approaches for risk maps can be applied to any taxon with available data on their distribution and ecological impacts. Our approach can be used to identify and prioritise sites with potential high impact. Based on the future risk map, we suggest five management strategies to limit the expansion of impactful species, of for clearing impactful species.